Pomodoro Technique Analysis in Zoom-Based Classrooms - Nyak Mutia Ismail; Zaiyana Putri; Anita Noviyanti (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2022)
This study aimed at finding out students’ state of motivation, engagement, and time management when Pomodoro teaching technique is implemented in ZOOM-based synchronous classroom. This study is naturally qualitative as it investigates the data from students’ during online learning as individual experiences. There were 53 freshman students from various majors involved in this study who had to attend ZOOM classroom for General English Course from August to December 2021. Ten meetings with the implementation of Pomodoro were carried out. In carrying out Pomodoro technique, the students were given break-time for 5 minutes in every 25-minute learning session. Afterwards, the students should answer the questionnaire consisting of 30 statements asking about motivation, engagement, and time management. Once the data collected, they were analyzed using Interactive Analysis (data reduction, data display, and data verification). The results uncover that, regarding motivation, 33 students had positively-oriented motivation; then in term of learning engagement, 40 students were actively engaged with online learning activities given; and concerning time management, 32 students had good time management. This result apparently implies thatnon-physical meeting—which lecturers probably presume that less stress is employed—demands regular break as well. Thence students can still learn efficiently and effectively.